A retrospective study of SARS-CoV-2 seroprevalence in dogs and cats in the Community of Madrid, Spain - Sánchez-Morales, Lidia; Sánchez-Vizcaíno, José M.; Domínguez, Lucas; Barroso-Arévalo, Sandra (Frontiers in Microbiology, 2023)
To date, susceptibility to SARS-CoV-2 infection in domestic animals including cats and dogs has been described. However, it is important to carry out passive surveillance of these animals to be aware of any changes in the outcomes of the disease in these species that may occur. In this study, we have performed a retrospective study in which we analyzed sera (n=1,640) from random animals: dogs (n=1,381) and cats (n=259) belonging to both homes (n=1,533) and animal protection centers (n=107) in the Community of Madrid, Spain. Neutralizing antibodies were evaluated between November 2021 and May 2022 using a surrogate ELISA kit to determine the seroprevalence. Based on the results obtained, a few animals (both cats and dogs) presented neutralizing antibodies to SARS-CoV-2 (2.3%), all of them from private owners. However, the seroprevalence in cats (4.6%) resulted to be almost twice as much as in dogs (1.9%) which reinforces that cats' susceptibility to the infection seems higher than in the case of dogs, maybe due to the lower ACE2 expression of the dogs in the respiratory tract. These findings also confirm that the probability of infection is considerably higher in domestic animals in close contact with infected owners, compared to animals living in animal shelters whose contact with humans is markedly lower.